In vitro and in vivo dose-dependent inhibition of methylmercury on glutamine synthetase in the brain of different species - Kwon, OS; Park, YJ (ELSEVIER SCIENCE BV, 2003)
Glutamine synthetase (GS) catalyzes the synthesis of glutamine from glutamate and ammonia and is associated with ischemic injury and neurological diseases. We investigated whether the in vitro and in vivo exposure to methylmercury (MeHg) produce changes in GS activity in the brain of different species. The brain in rats and mice was dissected into different regions for GS assay. MeHg levels in the brain tissues and blood of mice treated 2, 4 or 10 mg/kg MeHg were determined by a gas-chromatography/mass selective detector. In vitro exposure of MeHg (0.1 - 100 muM) produced dose-dependent decreases of GS activity in rat brains with 50% inhibition occurred at 10-20 muM. MeHg was a more potent GS inhibitor in vitro in the rat brain than other GS inhibitors (e.g., methionine sulfoximine, kainic acid). These effects were further confirmed using purified GS of sheep brains. In vivo GS activity was also inhibited in the hippocampus of mice given 4 or 10 mg/kg of MeHg. In mice concentration ratios of brain tissues to blood were 0.05-0.14 at 24 It post-dose. These data showed that MeHg produced significant changes in GS activity, indicating that GS is an effective biomarker for MeHg exposure. (C) 2003 Elsevier Science B.V. All rights reserved.